Spurious Ampicillin Resistance by Testing Haemophilus influenzae with Agar Containing Supplement C - Washington, John A. (1976)
Ampicillin resistance (minimal inhibitory concentration ≥10 μg/ml) in the absence of beta-lactamase activity by Haemophilus influenzae was noted in tests performed with Mueller-Hinton agar containing one lot of supplement C. All strains, except five with known resistance due to beta-lactamase activity, were inhibited by 0.6 μg or less of ampicillin per ml of chocolatized blood agar.